The COMT Genetic Factor Regulates Chemotherapy-Related Prospective Memory Impairment in Survivors With HER2−/+ Breast Cancer - Li, Wen; Zhang, Qianqian; Cai, Yinlian; Chen, Tingting; Cheng, Huaidong (Frontiers in Oncology, 2022)
Background: Previous findings indicated that polymorphism in gene catechol-O-methyltransferase (COMT) had been linked to chemotherapy related cognitive impairment (CRCI). Nevertheless, the motivation of COMT polymorphisms in regulating cognitive impairment in breast cancer survivors with disparate status of human epidermal growth factor receptor 2(HER2) was still vague. Objective: The current research aimed to evaluate the regulation of the risk by COMT genotype on CRCI in breast cancer survivors with disparate status of HER2. Methods: Breast cancer survivors (103 with HER2- and 118 with HER2+) performed neuropsychological tests before and after chemotherapy, containing event-based and time-based prospective memory (EBPM, TBPM). Three single-nucleotide polymorphisms (SNPs) were estimated by providing peripheral blood, containing COMT (rs165599, rs737865 and rs4680). Results: The EBPM and TBPM performances was lower as compared with these before chemotherapy (z=-7.712, z = -2.403, respectively, p< 0.01). Further, the EBPM and TBPM performances of HER2- group survivors were lower than these of HER2+ group survivors after chemotherapy (z=-7.181,p<0.01;z =-2.205 p<0.05, respectively). The survivors with COMT (rs165599) A/A genotype carriers had a meaningfully poorer chance of memory descend (dominant model: adjusted, OR=2.21, CI (95%) =1.156-4.225, p =0.016), showed better on TBPM test, relative to G/G genotype. Patients with the COMT (rs737865) A/G and G/G genotype showed protective function than the patients with the A/A, performed better on MMSE and TBPM tests. Conclusion: The types of HER2 may be correlated to chemotherapy related prospective memory impairments in breast cancer survivors. Further, the COMT( rs165599,rs737865) polymorphism were correlated to the risk of TBPM decline scores, and possible be a potential genetic identifying for increasing risk of CRCI in breast cancer patients with disparate status of HER2.